CONTEXTUALIZATION OF GAMBLING IN THE TRADITION OF CHINESE SOCIETY IN BANGKA - Sirait, Suriadi; Sunggara, Adystia (JCH (Jurnal Cendekia Hukum), 2024)
This study analyses the gambling tradition in the Chinese community in Bangka using a socio-legal approach to understand the implementation of Article 303 of the Criminal Code (KUHP). The gambling tradition in Chinese culture is often not only viewed as an economic activity but also as part of a social ritual involving specific cultural values. This study focuses on three main aspects: first, a historical and cultural exploration of the background of the gambling tradition in the Chinese community in Bangka; second, a legal review of the implementation of Article 303 of the Criminal Code which regulates gambling in the local context; and third, an analysis of how harmonization between positive legal norms and local cultural norms can be achieved in enforcing gambling-related laws. This text research applies a qualitative method with a descriptive-analytical approach involving interviews, literature reviews, and legal document analysis. The results of the study indicate that the repressive approach in the implementation of Article 303 of the Criminal Code often does not fully pay attention to the local cultural context, so the Restorative Justice Framework for Cultural Integration method is needed as an alternative solution in resolving conflicts between legal and cultural norms.